Trade-offs between benefits and costs of forest proximity: farmers' practices and strategies regarding tree-crop integration and ecosystem disservices management - Mulatu Osie (Resilience Alliance, 2020)
The impact of ecosystem disservices is among the issues that farmers have to consider in management of livelihoods and local landscapes. We investigated distinct practices developed within local communities in tree-crop integration and strategies to offset disservices. Forty-eight transects (24 at ≤1 km and 24 at ≥3 km from forest edges) were laid in the study sites. Woody and crop species were recorded from a total of 150 homegardens and farm fields along the 48 transects. In addition, farmers (n = 384) were interviewed using a semistructured questionnaire to assess their land-use practices and management strategies to counter ecosystem disservices. Data were analyzed using a linear mixed effects model of the statistical program R. A total of 72 woody and crop species belonging to 40 families were recorded. The mean number of woody species increased near to the forest. Wild mammals, such as olive baboons, bush pigs, warthogs, vervet monkeys, and porcupines were common crop raiders. Farmers used fences, guarding, noise, scare devices, and smoke to scare away crop-raiding animals. To protect beehives in the forest fragments, they have developed indigenous skills such as dusting ashes, spraying indigenous repellant suspensions, and destroying the nests of raiding ants. A biological control mechanism was also used by farmers where they cut part of the nest of Crematogaster sp. (locally called "Penie") and glue it onto the trunk of trees with beehives. Crematogaster sp. safeguard the beehives from raiding ants as part of their efforts to protect their own nests. We recommend both ecological and socioeconomic studies in order to augment farmers' strategies to balance disservices and corresponding management practices across the landscapes.